Comparison of Flexible Ureterorenoscopy and Mini Percutaneous Nephrolithotomy in the Management of Multiple Renal Calculi in 10-30 mm Size - Yanaral, Fatih; Ozgor, Faruk; Kucuktopcu, Onur; Sarilar, Omer; Ayranci, Ali; Savun, Metin; Yuksel, Bahar; Binbay, Murat (Urology Journal, 2019)
Purpose: To evaluate the efficacy and safety of flexible ureterorenoscopy (f-URS) and mini percutaneous nephrolithotomy (mini-perc) in the management of 10-30 millimeter multiple renal stones. Materials and Methods: The charts of patients who underwent f-URS or mini-perc for multiple kidney stones between January 2011 and July 2015 were retrospectively analyzed. Patients with multiple 10-30–mm-sized renal stones were enrolled in the study. A total of 374 patients underwent mini-perc and 85 patients met the study inclusion criteria. In the same period, f-URS was performed in 562 patients, and 163 had 10-30–mm multiple renal stones. We selected 85 patients to serve as the control group from this cohort using propensity score matching with respect to the patient’s age, ASA score, number, size, and location of stones to avoid potential bias between groups. Results: The mean operation time and fluoroscopy screening time (FST) was significantly longer in the mini-perc group (P = .001 and P = .001, respectively). The mean hospitalization time was 76.9±38.7 hours in the mini-perc group and 25.0±27.7 hours in the f-URS group (P = .001). Post-operative complications, according to the Clavien classification system, were significantly more frequent in the mini-perc group (P = .003). The stone-free rate was 87% in the f-URS group and 83.5% in the mini-perc group (P = .66). Conclusion: Our study demonstrated that f-URS and mini-perc were effective treatment options for multiple renal stones 10-30 mm in size. However, f-URS was associated with a significantly lower complication rate, shorter operation time, shorter FST, and shorter hospitalization time.